Molecular epidemiology of Hepatitis B virus, Hepatitis C virus, and Hepatitis D virus in general population of Afghanistan - Husseini, Abbas Ali; Saeed, Khwaja Mir Islam; Yurdcu, Esra; Bozdayı, A. Mithat (Turkish Journal of Gastroenterology, 2020)
Background/Aims: This study gives a clue about genotypes, subgenotypes and subtypes of HBV, HCV and HDV viruses in general population of Afghanistan. Materials and Methods: A total of 234 HBsAg, 44 anti-HCV and 5 Anti-Delta positive patients belong to 25-70 age group were obtained through a rapid screening test among 5898 residents of Afghanistan. After quantifying viral load, genotyping of 61 HBV, 29 HCV and 1 HDV samples were accomplished by sequencing of a segment of the HBV Pre S, HCV NS5B, and HDV Delta antigen regions respectively. Clinically important variants of the HBV polymerase gene, the “a” determinant of HBsAg, HCV NS5B and NS3 regions were assessed. Results: All HBV isolates were dispersed throughout the genotype D branch and ayw2 was the only subtypes found. The anti-HDV prevalence among HBsAg positive individuals was 2.2% and the single HDV sample, belonged to HDV genotype I. Analysis of HCV isolates revealed subtype HCV-1b in 75.86%, HCV-3a in 20.69% and HCV-3b in 3.44% patients. The observed mutant variants in the MHR of HBsAg were Y100 15%, Q101 5%, G102 15%, T115 45%, P120 5%, T131 5%. Likewise, S213T 10%, Q215P 5% and N248H 100% mutations were detected in the HBV polymerase region. C316N mutation was prevalent in 72.7% of HCV 1b participants. Conclusion: Genotypic variation in Afghan patients is in line with the ones existing in neighboring countries and regions. HBV genotypes D1, subtype ayw2, HDV RNA type I, and HCV RNA genotype 1b are likely to be dominant in Afghan patients.